2007
DOI: 10.1002/ajpa.20636
|View full text |Cite
|
Sign up to set email alerts
|

Protection of obstetric dimensions in a small‐bodied human sample

Abstract: In human females, the bony pelvis must find a balance between being small (narrow) for efficient bipedal locomotion, and being large to accommodate a relatively large newborn. It has been shown that within a given population, taller/larger-bodied women have larger pelvic canals. This study investigates whether in a population where small body size is the norm, pelvic geometry (size and shape), on average, shows accommodation to protect the obstetric canal. Osteometric data were collected from the pelves, femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
143
1
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(169 citation statements)
references
References 48 publications
13
143
1
12
Order By: Relevance
“…The Andaman Islanders exhibit a very narrow pelvis (BIB) similar to the Khoisan, which is both absolutely narrow and narrow relative to limb lengths. Previous studies have investigated the narrow pelvic dimensions of the Andaman Islanders and Khoisan/ LSA Southern Africans (Kurki 2007(Kurki , 2011 but it is somewhat surprising that this characteristic is not shared with other small-bodied foragers such as the Aeta. Pelvic dimensions have recently been shown to carry phylogenetic information relevant to human population history (Betti et al 2012(Betti et al , 2013; however, we know very little about the mechanisms controlling other skeletal dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The Andaman Islanders exhibit a very narrow pelvis (BIB) similar to the Khoisan, which is both absolutely narrow and narrow relative to limb lengths. Previous studies have investigated the narrow pelvic dimensions of the Andaman Islanders and Khoisan/ LSA Southern Africans (Kurki 2007(Kurki , 2011 but it is somewhat surprising that this characteristic is not shared with other small-bodied foragers such as the Aeta. Pelvic dimensions have recently been shown to carry phylogenetic information relevant to human population history (Betti et al 2012(Betti et al , 2013; however, we know very little about the mechanisms controlling other skeletal dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…While the selection of a large, obstetrically capacious pelvis might conflict with the thermoregulatory needs of a narrow pelvis in hot climates, such a dilemma might not present itself in cold climates, where a large pelvis would be climatically favored (Weaver and Hublin, 2009). Obstetrical constraints, if stronger in small-bodied populations as suggested by Kurki (2007), could increase pelvic dimorphism in these populations in respect to others characterized by larger body size. In a larger study, Kurki (2011) found only two pelvic measurements that appeared to be more sexually dimorphic in small-bodied populations than in larger-bodied ones: the anterior-posterior dimensions of the midplane and outlet, both obstetrically relevant dimensions.…”
mentioning
confidence: 90%
“…Kurki (2007) compared body size and pelvic dimensions in three populations that ranged from small (KhoeSan), through medium (Portuguese), to large body size (European-Americans). Kurki's results showed that some dimensions of the birth canal, especially of the midplane and outlet, are not significantly smaller in KhoeSan women relative to the other two populations, despite the former being significantly smaller in body size and in most of the other pelvic measurements (Kurki, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Th e relationships of these dimensions in males are not presented in literature. In addition, the most part of the studies on the relationships among parameters was performed on skeletal collections without taking into account pelvic joints [5,6,10,17]. Th erefore, this study focuses on two aspects of the prediction of the bispinous diameter: 1) the relationship between the false pelvis and the true pelvis, which is not explored in males; 2) the sexual dimorphism in this prediction, which seems to be topical for measures in live humans.…”
Section: Introductionmentioning
confidence: 99%